Telling Tales of War to Teens: Ignacio Martínez de Pisón's Una guerra africana and Morocco as "Open Wound" in the Spanish National Imaginary - Silvia Bermúdez (Studies in 20th & 21st Century Literature, 2006)
Exactly ten years after its traumatic defeat in the Spanish-American War of 1898, Spain appeared to find some compensation for the loss of its last colonies by undertaking the invasion of Morocco in 1908. The enterprise proved difficult when the forces of Abd-el-Krim defeated the Spanish army in the summer of 1921. This terrible loss was metaphorized as an "open wound" and entered the collective imagination by becoming a theme in novels such as José Díaz Fernández's El blocao (1928), Ramón Sender's Imán (1930), and Arturo Barea's series La forja de un rebelde (1941-1944). Known as the "Disaster of Annual," the defeat appeared to be almost forgotten until a series of narratives in the late twentieth and early twenty-first centuries obsessively returned to this particular moment of Spanish history. I focus on how one such narrative, Martínez de Pisón's Una guerra africana (2000), revisits this war as adolescent literature ("novelas juveniles") and within the literary genre of the "novels of the War in Africa," and by so doing, contributes to the articulation of a Spanish collective identity with the historical memory of the feared Moroccan Other.
Keywords: Martínz de Pisón; Spanish-American War; Morocco; José Díaz Fernández; El blocao; Ramón Sender; Imán; Arturo Barea; La forja de un rebelde; una guerra africana; adolescent literature; novelas juveniles; novels of the War in Africa; Spanish identity; Moroccan Other